Dysregulation of FBW7 in malignant lymphoproliferative disorders - Wan, Xin; Guo, Wei; Zhan, Zhumei; Bai, Ou (Frontiers in Oncology, 2022)
The ubiquitin-proteasome system (UPS) is involved in various aspects of cell processes, including cell proliferation, differentiation, and cell cycle progression. F-box and WD repeat domain-containing protein 7 (FBW7), as a key component of UPS proteins and a critical tumor suppressor in human cancers, controls proteasome-mediated degradation by ubiquitinating oncoproteins such as c-Myc, Mcl-1, cyclin E, and Notch. It also plays a role in the development of various cancers, including solid and hematological malignancies, such as T-cell acute lymphoblastic leukemia, diffuse large B-cell lymphoma, and multiple myeloma. This comprehensive review emphasizes the functions, substrates, and expression of FBW7 in malignant lymphoproliferative disorders..